ANALISIS PENGARUH KEPADATAN PENDUDUK, PENGELUARAN PERKAPITA DAN TINGKAT PENGANGGURAN TERBUKA TERHADAP PENDUDUK MISKIN DI PROVINSI ACEH TAHUN 2000-2019 - Munira munira; Hijri Juliansyah (Jurnal Ekonomi Regional Unimal, 2022)
This study examined the relationship between population density, per capita expenditure, open unemployment rate, and the poor people in Aceh province. This study used secondary data from 2000 to 2019. The data were analyzed using the Vector Autoregression (VAR) analysis method with the help of Eviews 10. The results indicated that population density had no positive and significant effect on the poor people, per capita expenditure had a positive but insignificant effect on the poor people, and the open unemployment rate had a positive and significant effect on the poor people.